Development, characterization and in vitro applications of a thymus cell line from Pangasianodon hypophthalmus (Sauvage 1878) - SONI, PANKAJ; PRADHAN, PRAVATA K; SOOD, NEERAJ (The Indian Journal of Animal Sciences, 2023)
Pangasianodon hypophthalmus is an economically important catfish species cultured in India. In the present study, a continuous cell line from the thymus of P. hypophthalmus (PHT) was established using the explant method and subcultured 52 times since development. PHT cells showed optimal growth in L-15 medium containing 20% fetal bovine serum at 28°C. The species of the cell line from striped catfish was confirmed through PCR amplification and sequencing of 16S, and COI genes. The cell line was found to be Mycoplasma free. The modal chromosome number of PHT cells was 60 (2n). Immunophenotyping using different antibodies showed the epithelial nature of the cells. Cytotoxicity of arsenic and mercury was assessed using Neutral red and MTT assay, which revealed reduced cell survival with an increase in toxicant concentration. Cells transfected successfully with the GFP reporter gene using lipofectamine reagent indicated the suitability of the cell line for expression studies. The cell line has been submitted to NRFC, Lucknow with accession no. NRFC-078 at ICAR-NBFGR, Lucknow. The developed cell line will have applications in suspected viral disease investigation, transgenic, and immunological studies.